Tingkat Kecukupan Energi dan Zat Gizi Pada Lansia - Oriza Aditya; Rafi farizki; Hanipah Hanipah (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2022)
Abstract – The population of elderly people continues to increase every year. This increase is a good result based on the country's efforts to increase the life expectancy of its population in the health sector. Adequacy of energy, nutrition and lifestyle have affected the physical health of the elderly. This research was conducted in an effort to analyze descriptively related to the adequacy of nutrition and energy for the elderly in Harjamukti District. The research method used is a quantitative cross sectional design. The research sample consisted of 100 elderly people who were selected purposively from Harjamukti District. Data collection was carried out through interview techniques using a structured questionnaire. Data analysis was carried out using a descriptive approach through a univariate test. The results showed that the average energy adequacy level for men was 48.77% and for women was 51.06% which in this case was in the less category. The average level of adequacy of macronutrients for the elderly including protein and carbohydrates is in the less category. In this case, only the average fat adequacy of the elderly is good with the percentage of men being 56.89% and women being 56.47%. The adequacy level of micronutrients including sodium and calcium is in the less category.